The Peculiar Disk Evolution of 4U 1630-472 Observed by Insight-HXMT During its 2022 and 2023 Outbursts - Peng, Jing-Qiang; Zhang, Shu; Shui, Qing-Cang; Chen, Yu-Peng; Zhang, Shuang-Nan; Kong, Ling-Da; Santangelo, A.; Yu, Zhuo-Li; Ji, Long; Wang, Peng-Ju; Chang, Zhi; Li, Jian; et al. (The Astrophysical journal, 2024)
We study the spectral properties of the black hole X-ray transient binary 4U 1630–472 during its 2022 and 2023 outbursts with Insight-HXMT observations. We find that the outbursts are in peculiar soft states. The effect of the hardening factor on the disk temperature is taken into account by the kerrbb model, and the flux and temperature of the disk are found to follow F ∝ T eff 3.92 ± 0.13 and F ∝ T eff 4.91 ± 1.00 for the two outbursts, respectively. The flux–temperature relation is roughly consistent with a standard disk. By fitting with a p -free model, the p -value, the exponent of the radial dependence of the disk temperature, is found to have an anticorrelation with disk temperature. Combining a joint diagnostic analysis with a diagram of the relation between the nonthermal fraction and luminosity, we find a possible scenario that the disk evolves from 2022 to 2023 toward a slim one with a decreasing radiation efficiency, where such an evolution may depend on the fraction of the nonthermal emission in the high soft state.